Seven new southeastern Brazilian species of Myrcia (Myrtaceae) - Sobral, Marcos; Caliari, Cláudia P.; Gressler, Eliana; Mazine, Fiorella F.; Magenta, Mara; Viana, Pedro L. (Phytotaxa, 2016)
There are described, illustrated, compared with related species and commented in their conservation issues Myrcia delicata, M. exapata, M. guarujana, M. parca, M. pseudosplendens, M. ubatubana and M. venosissima. Myrcia delicata, from the states of São Paulo and Rio de Janeiro, is close to M. neocambessedeana, differing through its triflorous, slender inflorescences; Myrcia exapata, from Rio de Janeiro, is related to M. calycampa, differing through its obovate blades, longer peduncles and dichasial branches; Myrcia guarujana, from São Paulo, is related to M. colpodes, but differs in its pilose flowers and trilocular ovaries; Myrcia parca, from the state of Espírito Santo, is related to M. warmingiana, but differs in its narrower, concolorous blades, pauciflorous inflorescences and smooth ovaries; Myrcia pseudosplendens, from Minas Gerais, is close to M. splendens, but has costate fruits and exfoliating bark; Myrcia ubatubana, from São Paulo, is related to M. ferruginosa, but is kept apart through its pauciflorous inflorescences and narrower blades, and Myrcia venosissima, from Minas Gerais, resembles M. almasensis, differing through its uniflorous to triflorous inflorescences and flowers with longer calyx lobes.